2014
DOI: 10.1111/hpb.12151
|View full text |Cite
|
Sign up to set email alerts
|

Interventional treatment of a biliary stricture after adult right-lobe living-donor liver transplantation with duct-to-duct anastomosis

Abstract: The incidence of overall biliary stricture was related to bile leakage and the urgency of the surgery. All biliary strictures could be treated by interventional modalities. These approaches are effective, complementary and help to avoid the need for surgery for a biliary stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 23 publications
5
32
2
1
Order By: Relevance
“…Endoscopic management of biliary anastomotic strictures following RL LDLT is technically difficult most of the time, and recent studies have reported a technical success rate of 46.7%‐81.5% . In the present study, the technical and clinical success rates were generally in agreement with those of the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Endoscopic management of biliary anastomotic strictures following RL LDLT is technically difficult most of the time, and recent studies have reported a technical success rate of 46.7%‐81.5% . In the present study, the technical and clinical success rates were generally in agreement with those of the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Other risk factors for BAS identified in multivariate analyses include donor age [50 years [8], preoperative MELD score C35 [27], urgency of the surgery [33], bile duct diameter [34], a graft with multiple bile ducts [31], graft cold ischemia time [24,34], hepatic artery stenosis [31], and acute cellular rejection [24]. Whether the biliary reconstruction technique affects the development of BAS is controversial.…”
Section: Etiologies and Risk Factors For Biliary Strictures After Ldltmentioning
confidence: 99%
“…The results of balloon dilation followed by PS placement for BAS have been variable, with technical endoscopic and final endoscopic success rates ranging from 40-84% and from 20-100%, respectively [26,28,31,33,54,[62][63][64]. Technical endoscopic success is defined as successful placement of biliary stents without the aid of a percutaneous procedure (i.e., rendezvous technique), and final endoscopic success is resolution of BAS after stent removal.…”
Section: Plastic Stent Placementmentioning
confidence: 99%
See 2 more Smart Citations